Pseudohalide‐Controlled Assemblies of Copper–Schiff Base Complexes with an Encapsulated Sodium Ion: Synthesis, Crystal Structure, and Computational Studies. Issue 4 (4th December 2012) - Maiti, Monami; Sadhukhan, Dipali; Thakurta, Santarupa; Sen, Shubhatam; Zangrando, Ennio; Butcher, Ray J.; Deka, Ramesh C.; Mitra, Samiran
Abstract: Three new hetero‐bimetallic coordination complexes [Na(Cu II L 1 )2 ](ClO4 )· 0.5H2 O (1 ), [Na(Cu II L 2 )2 ][Cu I 2 (μ1, 3 ‐NCS)3 ] n (2 ), and [Na(Cu II L 3 )2 ](μ1, 5 ‐dca) n (3 ; dca = dicyanamide) have been synthesized by using different Schiff base ligands [e.g., L 1 H2 = N, N′ ‐bis(3‐methoxysalicylidenimino)‐1, 3‐diaminopentane, L 2 H2 = N, N′ ‐bis(3‐ethoxysalicylidenimino)‐1, 3‐diaminopropane, andL 3 H2 = N, N′ ‐bis(5‐bromo‐3‐methoxysalicylidenimino)‐1, 3‐diaminopropane] in the presence of pseudohalide coligands N3 –, SCN –, and N(CN)2 – (dca), respectively. The ligands and the complexes have been characterized by microanalytical and spectroscopic techniques. The structures of the complexes, determined by single‐crystal X‐ray diffraction studies, show that in all cases a trinuclear Na(Cu II L )2 unit is formed, but of different configurations.1 does not include N3 – anions. In contrast, in2, SCN – extrudes partial in situ reduction of Cu II to lead to the formation of an infinite [Cu I 2 (μ1, 3 ‐NCS)3 ] n anionic chain; and in3, N(CN)2 – bridges the metal–ligand assemblies to form a 1D polymeric chain. ESI‐MS, UV/Vis spectroscopy, and cyclic voltammetry were performed to investigate the solution‐state behavior of the complexes. Theoretical calculations of the optimized geometries of the complexes were carried out at the BLYP/DNP level to determine their relative stabilities from the HOMO–LUMO gap and chemical softness values. Abstract : Three new hetero trinuclearL Cu–Na–CuL cationic‐unit‐based complexes1 –3 with N2 O4 donor Schiff bases have been synthesized and characterized by spectroscopic techniques as well as single‐crystal X‐ray diffraction analysis. The CuL units interact to encapsulate the sodium ion in a propeller‐like fashion in1 and to sandwich the sodium in2 and3 .